Analysis of homogeneity and isotropy of the flow in the watercourses by applying the RAPS and IPTA methods - Bojan Đurin; Mirna Raič; Petra Sušilović; Hossein Banejad (Advances in Civil and Architectural Engineering)
Due to the frequent climatic changes occurring worldwide, which are related to extreme meteorological parameters as well as human activities, it is obvious that these influence the flow regimes of rivers. River flow is the most important factor determining the hydrological regime of any river. This has a substantial influence on the water resources and the environment surrounding the river. Hydrotechnical structures are also dimensioned on the basis of the flow as the primary input parameter. The flow conditions have different properties and correlations with the material of the river bed. In this paper, possible dependencies and phenomena are investigated using real case studies on two rivers in Croatia - examples of river courses in alluvium and karst areas - with regard to homogeneity and isotropy analyses. For this purpose, rescaled adjusted partial sums and innovative polygon trend analysis methods will be applied on the form of a combination of methods at the same watercourses. It has been shown that the analysed time series of the flows do not exhibit homogeneity and isotropy. In addition, fluctuations and irregularities were detected in the same time series. This is key information for determining the reliability of the flow forecast.